2018
DOI: 10.1002/nbm.3892
|View full text |Cite
|
Sign up to set email alerts
|

Increased hyperpolarized [1‐13C] lactate production in a model of joint inflammation is not accompanied by tissue acidosis as assessed using hyperpolarized 13C‐labelled bicarbonate

Abstract: Arthritic conditions are a major source of chronic pain. Furthering our understanding of disease mechanisms creates the opportunity to develop more targeted therapeutics. In rheumatoid arthritis (RA), measurements of pH in human synovial fluid suggest that acidosis occurs, but that this is highly variable between individuals. Here we sought to determine if tissue acidosis occurs in a widely used rodent arthritis model: complete Freund's adjuvant (CFA)‐induced inflammation. CFA robustly evoked paw and ankle swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
(127 reference statements)
1
13
0
Order By: Relevance
“…Inflamed rat paws exhibited a Lac/Pyr ratio of 0.52 ± 0.16 (mean ± SD) compared with control paws presenting a Lac/Pyr ratio of 0.32 ± 0.11. More recently, Wright and coworkers confirmed these results in CFA-induced joint inflammation in mice [11]. A higher Lac/Pyr ratio of 0.74 ± 0.32 (mean ± SD) was found in inflamed joints when measuring the entire signal coming from the inflamed feet of a small cohort of animals.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Inflamed rat paws exhibited a Lac/Pyr ratio of 0.52 ± 0.16 (mean ± SD) compared with control paws presenting a Lac/Pyr ratio of 0.32 ± 0.11. More recently, Wright and coworkers confirmed these results in CFA-induced joint inflammation in mice [11]. A higher Lac/Pyr ratio of 0.74 ± 0.32 (mean ± SD) was found in inflamed joints when measuring the entire signal coming from the inflamed feet of a small cohort of animals.…”
Section: Discussionmentioning
confidence: 63%
“…Metabolic reprogramming is a key feature of inflamed tissues, typically associated with reduced oxidation while favoring glycolysis and glutaminolysis [ 3 ], leading to high glucose demand, high lactate levels, and acidosis, directly contributing to cellular injury via proinflammatory signals [ 4 , 5 ]. While early metabolic changes in RA and the effects of anti-inflammatory treatment approaches can be monitored by molecular imaging using the gold standard 2-deoxy-2-[ 18 F]fluoro-D-glucose ( 18 F-FDG) positron emission tomography (PET) [ 6 9 ], only two studies investigated lactate production in preclinical models of RA but exclusively examined the advanced severe stage using hyperpolarized 1- 13 C-pyruvate magnetic resonance spectroscopic imaging (MRSI) [ 10 , 11 ]. In our studies, we examined the glucose-6-phosphate-isomerase (GPI)-serum-induced experimental RA to monitor the temporal dynamics of the effector phase of arthritic joint disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during inflammatory arthritis, FLS are located in an environment with abundant algogens that have been shown to signal through the modulation of TRP channels 9 and there is also mixed evidence in animals and humans for development of tissue acidosis. 3 , 24 , 66 TRP channels and acid sensors in FLS can increase intracellular [Ca 2+ ] 26 , 35 and therefore, we tested the sensitivity of mouse knee-derived FLS to a range of acidic pH stimuli, as well as the prototypic TRP channel agonists, capsaicin (TRPV1), cinnamaldehyde (TRPA1), and menthol (TRPM8) using Ca 2+ imaging. We found that both control and TNF-FLS responded to a range of pH solutions (pH 4.0—7.0) with an increase in intracellular [Ca 2+ ], with an increased percentage of TNF-FLS responding to acid than control FLS at pH 5.0 to 6.0 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One mL of CFA contains 1 mg of Mycobacterium tuberculosis-H37Ra, heat-killed and dried, 0.85 mL paraffin oil, and 0.15 mL mannide monooleate. [ 26 ] Weight variation, clinical severity (CS) of inflammation status, and fluorescence from mice were observed daily. Mice were sacrificed after 72 h of observation due to ethical reasons.…”
Section: Methodsmentioning
confidence: 99%